The Influence of Self Regulation on The Learning Interest of Class VIII Students in Social Studies Subjects at SMP Muhammadiyah 21 Serbelawan - Nurul Anisa Nasution; Ripho Delzy Perkasa; Hendri Fauza (STKIP Taman Siswa Bima, 2025)
This study aims to determine the extent to which self-regulation influences students' interest in learning social studies at SMP Muhammadiyah 21 Serbelawan. Learning effectiveness is not entirely stable if the internal factors of students are also unstable, which is influenced by a lack of interest within themselves. The main factor in achieving goals is the internal drive formed from self-regulation. According to Zimmerman, self-regulation is a spirit towards self-efficacy, self-satisfaction, and interest in what one does. Self-regulation involves an effort within oneself to achieve a goal with a good outcome, so self-regulation is closely related to one's interest in learning. The higher the interest in learning, the better the learning outcomes, which arise from good self-regulation. This study uses a quantitative approach with an ex post facto method. The test results show that the probability of significance in the t-test (partial) is 0.001, which is less than 0.05. Therefore, (alternative hypothesis) is accepted and (null hypothesis) is rejected. Thus, is accepted for each variable in this study, indicating a significant influence between self-regulation and learning interest among students at SMP Muhammadiyah 21 Serbelawan.